Dp71 contribution to the molecular scaffold anchoring aquaporine‐4 channels in brain macroglial cells. Issue 4 (28th November 2020) - Belmaati Cherkaoui, Mehdi; Vacca, Ophélie; Izabelle, Charlotte; Boulay, Anne‐Cécile; Boulogne, Claire; Gillet, Cynthia; Barnier, Jean‐Vianney; Rendon, Alvaro; Cohen‐Salmon, Martine; Vaillend, Cyrille
Abstract: Intellectual disability in Duchenne muscular dystrophy has been associated with the loss of dystrophin‐protein 71, Dp71, the main dystrophin‐gene product in the adult brain. Dp71 shows major expression in perivascular macroglial endfeet, suggesting that dysfunctional glial mechanisms contribute to cognitive impairments. In the present study, we investigated the molecular alterations induced by a selective loss of Dp71 in mice, using semi‐quantitative immunogold analyses in electron microscopy and immunofluorescence confocal analyses in brain sections and purified gliovascular units. In macroglial pericapillary endfeet of the cerebellum and hippocampus, we found a drastic reduction (70%) of the polarized distribution of aquaporin‐4 (AQP4) channels, a 50% reduction of β‐dystroglycan, and a complete loss of α1‐syntrophin. Interestingly, in the hippocampus and cortex, these effects were not homogeneous: AQP4 and AQP4ex isoforms were mostly lost around capillaries but preserved in large vessels corresponding to pial arteries, penetrating cortical arterioles, and arterioles of the hippocampal fissure, indicating the presence of Dp71‐independent pools of AQP4 in these vascular structures. In conclusion, the depletion of Dp71 strongly alters the distribution of AQP4 selectively in macroglial perivascular endfeet surrounding capillaries. This effect likely affects water homeostasis and blood–brain barrier functions and may thus contribute to the synaptic and cognitive defects associated with Dp71 deficiency. Main Points: Loss of dystrophin‐Dp71 impairs expression of AQP4 isoforms in perivascular glial endfeet of capillary, not in larger vessels. Expression of other dystrophin proteins or utrophin paralogues may compensate for Dp71 loss in large vessels.